Nicholas of Cusa and the End of the Conciliar Movement: A @Humanist Crisis of Identity - Biechler, James E. (Church history, 1975)
The ignominious end of the conciliar movement in the mid-fifteenth century strikes many contemporary historians and theologians as one of the tragedies in the history of western civilization. Having shown great promise as an instrument of ecclesiastical reform and credited with ending the scandalous Great Western Schism in 1417, the movement for all practical purposes reached an inglorious end with the signing of the Concordat of Vienna in 1448. Though the tragic dimensions of the movement's demise are somewhat diminished by the truth of Tierney's conjecture that “the merely constitutional reforms emphasized in the conciliar programme could not have produced the much-needed regeneration in the whole life of the Church”, one is nevertheless inclined to view with sadness the neutralization of the nascent democratic aspirations which conciliarism represented.